Aerobic exercise improves sleep in U. S. active duty service members following brief treatment for posttraumatic stress disorder symptoms - Young-McCaughan, Stacey; Straud, Casey L.; Bumstead, Susannah; Pruiksma, Kristi E.; Taylor, Daniel J.; Jacoby, Vanessa M.; Yarvis, Jeffrey S.; Peterson, Alan L. (Frontiers in Psychology, 2023)
Introduction: Physical exercise is a lifestyle intervention that can positively impact aspects of physical and psychological health. There is a growing body of evidence suggesting that physical exercise, sleep, and PTSD are interrelated. This study investigated possible relationships. Three research questions were posed: (1) Did randomization to an aerobic exercise intervention reduce insomnia more than being randomized to an intervention without exercise, (2) Did change in sleep predict change in PTSD symptoms, and (3) Did change in sleep impact the relationship between exercise and PTSD symptom reductions? Methods: Data were collected from 69 treatment-seeking active duty service members with PTSD symptoms randomized into one of four conditions; two conditions included aerobic exercise, and two conditions did not include exercise. Participants in the exercise groups exercised five times per week keeping their heart rate >60% of their heart rate reserve for 20-25 minutes. Results: At baseline, 58% of participants reported moderate or severe insomnia. PTSD symptom severity decreased following treatment for all groups (p < .001). Participants randomized to exercise reported greater reductions in insomnia compared to those in the no exercise group (p = 0.47). However, change in insomnia did not predict change in PTSD symptoms nor did it significantly impact the relationship between exercise and PTSD symptom reductions. Discussion: Adding exercise to evidence-based treatments for PTSD could reduce sleep disturbance, a characteristic of PTSD not directly addressed with behavioral therapies. A better understanding of exercise as a lifestyle intervention that can reduce PTSD symptoms and insomnia is warranted.